MicroRNA in Pancreatic Cancer: From Biology to Therapeutic Potential - Rawat, Manmeet (Genes (Basel), 2019)
Pancreatic cancer is one of the most aggressive malignancies, accounting for more than 45,750 deaths annually in the U.S. alone. The aggressive nature and late diagnosis of pancreatic cancer, coupled with the limitations of existing chemotherapy, present the pressing need for the development of novel therapeutic strategies. Recent reports have demonstrated a critical role of microRNAs (miRNAs) in the initiation, progression, and metastasis of cancer. Furthermore, aberrant expressions of miRNAs have often been associated with the cause and consequence of pancreatic cancer, emphasizing the possible use of miRNAs in the effective management of pancreatic cancer patients. In this review, we provide a brief overview of miRNA biogenesis and its role in fundamental cellular process and miRNA studies in pancreatic cancer patients and animal models. Subsequent sections narrate the role of miRNA in, (i) cell cycle and proliferation; (ii) apoptosis; (iii) invasions and metastasis; and (iv) various cellular signaling pathways. We also describe the role of miRNA’s in pancreatic cancer; (i) diagnosis; (ii) prognosis and (iii) therapeutic intervention. Conclusion section describes the gist of review with future directions.